2010
DOI: 10.1002/cncr.25710
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of belotecan, a camptothecin analogue, in combination with carboplatin for the treatment of recurrent ovarian cancer

Abstract: BACKGROUND: Belotecan (CKD602; Camtobell, Chong Keun Dang Corp., Seoul, Korea) is a recently developed camptothecin derivative with antitumor properties. This phase II study was designed to evaluate the toxicity and efficacy of belotecan combined with carboplatin in patients with recurrent epithelial ovarian cancer (EOC). METHODS: Thirty-eight patients with recurrent EOC were treated with belotecan 0.3 mg/m 2 /day (days 1-5) and carboplatin AUC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Choi et al. [38] demonstrated that belotecan, a newly developed camptothecin analog, showed potent efficacy in combination with carboplatin for recurrent ovarian cancer patients at phase II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al. [38] demonstrated that belotecan, a newly developed camptothecin analog, showed potent efficacy in combination with carboplatin for recurrent ovarian cancer patients at phase II.…”
Section: Discussionmentioning
confidence: 99%
“…Su and coworkers [37] reported that noscapine, an opium alkaloid, increased cisplatin-induced apoptosis and inhibition of cell proliferation through the inactivation of hypoxia-induced factor 1 alpha (HIF-1a) transcription in C13K ovarian cancer cells. Choi et al [38] demonstrated that belotecan, a newly developed camptothecin analog, showed potent efficacy in combination with carboplatin for recurrent ovarian cancer patients at phase II.…”
Section: Discussionmentioning
confidence: 99%
“…BP had better response (66.7%, 14/21) than B (15.4%, 2/13) for platinum‐sensitive disease ( P = 0.004), but it was not superior in terms of progression‐free survival (BP, 6 months; B, 7 months). Both BP and B seemed to be effective and safe regimens for patients with platinum‐sensitive or ‐resistant recurrent ovarian cancer . The combined regimen of belotecan followed by oral etoposide for patients with platinum‐resistant or heavily treated ovarian cancer, fallopian tubal cancer, and primary peritoneal cancer, showed promising activity at dosage of 50 mg of oral etoposide …”
Section: Discussionmentioning
confidence: 99%
“…Both BP and B seemed to be effective and safe regimens for patients with platinum-sensitive or -resistant recurrent ovarian cancer. 4,5 The combined regimen of belotecan followed by oral etoposide for patients with platinum-resistant or heavily treated ovarian cancer, fallopian tubal cancer, and primary peritoneal cancer, showed promising activity at dosage of 50 mg of oral etoposide. 6 Compared to topotecan-based chemotherapy, belotecan-based chemotherapy has shown efficiency with acceptable toxicity in recurrent epithelial ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicites included neutropenia (28.8%), thrombocytopenia (19.8%) and anemia (14.4%). The addition of carboplatin to belotecan nearly doubled the response rate, while toxicities remained similar [40].…”
Section: Immunomodulatory Thalidomide Analog: Lenalidomidementioning
confidence: 96%